2012
DOI: 10.1007/s10549-012-1980-1
|View full text |Cite
|
Sign up to set email alerts
|

The single-nucleotide polymorphisms +936 C/T VEGF and −710 C/T VEGFR1 are associated with breast cancer protection in a Spanish population

Abstract: Vascular endothelial growth factor (VEGF) is a potent regulator of angiogenesis and thereby involved in the development and progression of solid tumours. The association between polymorphisms of angiogenesis pathway genes and risk of breast cancer (BC) has been widely studied, but the results are not conclusive. This information is especially limited in Spanish women, so we decided to conduct a case-control study. Here, we selected four commonly studied polymorphisms in VEGF, rs3025039 (known as +936 C/T), rs1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 41 publications
4
25
2
Order By: Relevance
“…The rs1570360 G̸A VEGF polymorphism, but not rs3025039 C̸T, was associated with an increased risk of breast cancer. A case-control study conducted by Rodrigues et al (28) suggested that the VEGF rs3025039 C̸T genotype was likely a key genetic marker of susceptibility to breast cancer in Caucasians. The data obtained from that study also indicated that the VEGF rs833052 C̸A polymorphism was not a susceptibility factor for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The rs1570360 G̸A VEGF polymorphism, but not rs3025039 C̸T, was associated with an increased risk of breast cancer. A case-control study conducted by Rodrigues et al (28) suggested that the VEGF rs3025039 C̸T genotype was likely a key genetic marker of susceptibility to breast cancer in Caucasians. The data obtained from that study also indicated that the VEGF rs833052 C̸A polymorphism was not a susceptibility factor for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The associations between three VEGF gene polymorphisms (-634 G/C, +936 C/T, and +1612 G/A) and breast cancer risk have been extensively studied, and the currently available results are inconclusive (Krippl et al, 2003;Jin et al, 2005;Lu et al, 2005;Jacobs et al, 2006;Kataoka et al, 2006;Eroglu et al, 2008;Jakubowska et al, 2008;Langsenlehner et al, 2008;Schneider et al, 2008;Wehrschuetz et al, 2009;Gu and Wang, 2011;Jin et al, 2011;Liu et al, 2011;Oliveira et al, 2011;Qiu et al, 2011;Wang et al, 2011;Yang et al, 2011;Rodrigues et al, 2012). The aim of this study was to investigate the association between three VEGF gene polymorphisms and breast cancer risk in Chinese Han patients.…”
Section: Introductionmentioning
confidence: 96%
“…VEGF-A is highly polymorphic in the promoter and 5¢ untranslated region and single-nucleotide polymorphisms in this region have been reported to regulate VEGF expression via alternative initiation of transcription and internal initiation of translation (Akiri et al, 1998;Huez et al, 1998). Polymorphisms of VEGF have been studied with disparate results in various diseases like type 2 diabetes (Awata et al, 2002;Buraczynska et al, 2007), giant cell arteritis (Rueda et al, 2005), renal complications in Henoch-Schonlein purpura (Rueda et al, 2006), hepatocellular carcinoma (HCC) (Kong et al, 2007), prostate cancer (Onen et al, 2008), familial endometriosis (Zhao et al, 2008), ectopic pregnancy (Elito et al, 2010), glomerulonephritides (Safrankova et al, 2011), hypertension (Kim et al, 2012), age-related macular degeneration (Lu et al, 2012), and breast cancer (Lu et al, 2005;Jacobs et al, 2006;Langsenlehner et al, 2008;Schneider et al, 2008;Rodrigues et al, 2012).…”
mentioning
confidence: 99%